Status of Media in Teaching Physics in Selected Secondary Schools in Kaduna state, Nigeria - Pearce, Nathaniel Olugbolahan (Obafemi Awolowo University, 2014)
This study was designed to examine the availability, utilization of media for instruction and the problems connected with the use of media for teaching physics in Kaduna State of Nigeria. Questionnaire, structures interview end participant observer scheme directed to the physics teachers, and randomly selected secondary schools students in Kaduna State were used for the collection of the data.